Pengembangan Karakter Berbasis Akhlak Mulia di Sekolah MAS Plus Al-Ulum Medan - Rahima, Titania (YPI Ulul Albab, 2025)
The development of character based on noble morals at MAS Al-Ulum Medan is a strategic effort to shape students who are not only academically excellent but also possess strong moral integrity. This program is designed through the integration of Islamic values into learning activities, daily routines, and exemplary behavior demonstrated by all members of the school community. Through a holistic approach that encompasses spiritual, emotional, and social aspects, the school is committed to instilling values such as honesty, responsibility, discipline, and respect for others. The results of this implementation show positive changes in students' attitudes and behaviors, which are reflected in their daily interactions both within and outside the school environment, thereby supporting the creation of a morally upright generation ready to face future challenges.